FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH DENGAN SISTEM PENGENDALIAN INTERN PEMERINTAH SEBAGAI VARIABEL MODERATING (Studi Empiris pada OPD Pemerintah Provinsi Riau) - Nuraini Nuraini; Kirmizi Kirmizi; Kamaliah Kamaliah (Program Studi Pendidikan Ekonomi Universitas Riau, 2019)
The objective of the research was to examine and analyze the influence of goodgovernment governance, the application of government accounting standard,competency of human resources and utilization of information technology withgovernment internal control system as moderating variable on the quality of financialof local government. The research use causality research method. The populationwas PPK-OPD (Financial Administrative Personal- Regional Device Organization),financial staff/Accounting staff, and treasurers in 35 OPDs in Riau ProvincialGovernment. The samples were 105 personel, taken by using total samplingtechnique. The data were gathered by using questionnaires and analysis of datausing SmartPLS. The result of the research showed that the application ofaccounting standard and utilization of information technology had positive andsignificant influence on the quality of financial reports of local government. Goodgovernment governance and competency of human resources are doesn’t affect toquality of financial reports of local government. Government internal control systemcouldn’t moderate the correlation of good government governance, the application ofgovernment accounting standards and utilization of information technology with thequality of financial reports of local government. Government internal control systemas moderating variable could strengthen the correlation of competency of humanresources to quality of local government financial reports of local government.